INFERRING EVOLUTIONARY RELATIONSHIPS AMONG DIFFERENT HUMAN PAPILLOMAVIRUS GENOTYPES FROM MULTIPLE ALIGNMENTS OF THE MAJOR CAPSID PROTEIN L1 - GABRIEL, Jane Eyre; FREITAS-LIDANI, Kárita Cláudia; DE FARIAS, Rodrigo Pessoa (Visão Acadêmica, 2019)
The major capsid protein L1 constitutes the entire exterior surface of the stabilized mature human papillomavirus (HPV), mediating initial attachment to host tissues or cells, and become pliable enough to ultimately allow release of the viral genome into a new target cell. The purpose of this study was to infer evolutionary relationships among different variable-risk HPV genotypes from comparative alignments of multiple sequences of the protein L1 deposited previously in biological information database. First, sequences of the protein L1 of 20 HPV genotypes were searched and selected from a non-redundant protein sequence database UniProtKB/Swiss-Prot. Next, a phylogenetic dendogram was constructed by comparing multiple sequences of the protein L1 using molecular evolutionary genetics analyses by Mega software. The dendogram generated from comparative alignments of the L1 protein sequences of different HPV types revealed the presence of two main clusters: a first cluster containing 12 HPV types linked intimately in several sub-branches and a second cluster grouping 8 HPV types linked in another sub-branches. Evolutionary groupings generated from L1 capsid protein sequences of variable-risk HPV genotypes demonstrated weak association between pathogenicity and phylogenetic proximity in the types analyzed, accompanied by low identity among their amino acid residues. The findings described herein reveal important insights into evolutionary patterns and phylogenetic relationships among variable-risk HPV genotypes for malignant conversion of virally infected cells from multiple alignments of the major viral capsid protein L1.